2023
DOI: 10.1101/2023.01.07.523104
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In VivoBiocompatibility of ZIF-8 for Slow Release via Intranasal Administration

Abstract: Zeolitic Imidazolate Framework-8 (ZIF-8) is becoming popular in research for its potential in antigen protection and for providing a thermally stable, slow-release platform. While papers applying these materials for immunological applications are aplenty in literature, studies that explore the biosafety of ZIF-8 in mammals - especially when administered intranasally - are not well represented. We checked the body clearance of uncoated and ZIF-coated liposomes and observed that the release slowed as ZIF-8 is ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Their findings indicated 90% cell viability, suggesting minimal toxicity. Kumari et al (2023) assessed the cytotoxicity of the lipopeptide biosurfactant on HEA 293 cells using MTT assay, revealing negligible cytotoxic effects. The amphiphilic nature of lipopeptides allows them to interact with cell membranes without disrupting their integrity significantly.…”
Section: O N L I N E C O P Y Cm Brinda Et Al: Biosurfactant Productio...mentioning
confidence: 99%
“…Their findings indicated 90% cell viability, suggesting minimal toxicity. Kumari et al (2023) assessed the cytotoxicity of the lipopeptide biosurfactant on HEA 293 cells using MTT assay, revealing negligible cytotoxic effects. The amphiphilic nature of lipopeptides allows them to interact with cell membranes without disrupting their integrity significantly.…”
Section: O N L I N E C O P Y Cm Brinda Et Al: Biosurfactant Productio...mentioning
confidence: 99%
“…The emergence of biomimetic mineralization of delicate biomaterials in a metal-organic framework (MOF) has allowed for the development of thermally and enzymatically protected biological material from numerous stressors. [24][25][26][27][28][29][30] Recent work has shown that the biofriendly zeolitic imidazolate framework-8 (ZIF-8)-encapsulated vaccines promote a more robust immune response against viral nanoparticles or whole-cell bacteria when injected subcutaneously. 24,25,[31][32][33] These results are striking, but in all cases, the vaccines used have been "self-adjuvanting" as the RNA or DNA within a virus or the lipopolysaccharides on the inactivated bacteria can induce their own strong immune response.…”
Section: Introductionmentioning
confidence: 99%
“…To ensure the stability and efficient transport of Zn(Bq) 2 , we used zeolitic imidazolate framework-8 (ZIF-8) as a drug carrier platform. ZIF-8 was chosen because of its exceptional characteristics such as ultrahigh porosity, large specific surface area, pH-induced biodegradability, and excellent biocompatibility ( 38 , 39 ). Furthermore, nanoscale ZIF-8 can prevent drug extravasation and renal clearance during transport.…”
Section: Introductionmentioning
confidence: 99%